Estimation of interferon gamma and some inflammatory atherogenic biomarkers levels in obese coronary atherosclerotic patients - Abdulrahman, Alia Talat; AL-Barzinji, Ruqaya Muhammed (Zanco Journal of Medical Sciences (ZJMS), 2020)
Background and objective: Coronary atherosclerosis is an inflammatory disease that may be caused by numerous factors. One of the most important factors is obesity; there are high concentrations of interferon gamma (IFN-γ) in obese patients. This study aimed to assess the levels of proinflammatory markers IFN-γ and high sensitive C- reactive protein (Hs-CRP) in obese coronary atherosclerotic patients and determine its correlation with lipid profiles. Methods: The present case-control study was carried out between December 2017 and May 2018 in the Cardiac Center-Surgical Specialty Hospital in Erbil city. It included 49 coronary atherosclerotic patients, 25 males and 24 females, and 39 controls. The sera were subjected to estimate of some inflammatory biomarkers including IFN-γ, Hs-CRP, and lipid profile such as total cholesterol, triglycerides, high-density lipoprotein cholesterol (HDL-C), low-density lipoproteins cholesterol (LDL-C) and very low- density lipoproteins (VLDL-C). Results: Serum concentrations of IFN-γ and Hs-CRP in coronary atherosclerotic patients were increased significantly than controls (P = 0.031, P = 0.001), respectively. Indeed the same above results were seen in obese coronary atherosclerotic patients and controls than non-obese coronary atherosclerotic patients controls. The mean concentration of lipid profile in obese coronary atherosclerotic patients was decreased than non -obese coronary atherosclerotic patients and controls, with no significant differences (P ≥0.05). There was a weak negative significant correlation between IFN-γ and HDL-C in obese coronary atherosclerotic patients (r= -0.456; P = 0.040). Conclusion: Proinflammatory cytokine as IFN-γ played a vital role in the pathophysiology of obese atherosclerotic patients in combination with Hs-CRP and LDL-C, which could be used as predictors for progressive the disease.